Local Variations of rainfall at Delhi (MAUSAM, 1961)
In this paper the results of analysis of the mean monthly rainfall recorded at four observatories, (1) Safdarjung Airport, (2) Lodi Road, (3) Palam Airport and (4) Delhi University, during the year 1956-59 have been given and discussed.